Inventory of greenhouse gas emissions from cattle, sheep and goats in Ethiopia (1994-2018) calculated using the IPCC Tier 2 approach - Wilkes, Andreas; Wassie, Shimels Eshete; Tadesse, Million; Assefa, Berhanu; Abu, Mustefa; Ketema, Asaye; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Livestock production is an important source of incomes and livelihoods for the rural population in Ethiopia, and is also an important contributor to greenhouse gas (GHG) emissions. Ethiopia’s GHG profile is dominated by emissions from the agriculture sector, representing 79% of total national emissions. Of these emissions, livestock accounts for the largest share (60%) due to enteric fermentation, manure management and emissions from managed soils due to livestock deposit of dung and urine.